Anxiety and depression symptoms and their association with discrimination and a lack of social support among first- and second-generation immigrant adolescents. (March 2022) - Abdulhamed, Rekar; Lonka, Kirsti; Hietajärvi, Lauri; Ikonen, Riikka; Klemetti, Reija
Abstract: The focus in the present study is on how experienced discrimination, being able to discuss personal matters with parents, and having someone to discuss personal worries with relate to symptoms of depression and generalized anxiety among first- and second-generation immigrant-background adolescents (aged 14–15) living in Finland. The data used was collected for the National School Health Promotion Study (2017) conducted by The Finnish Institute for Health and Welfare (N = 73, 690). Mental health was assessed on the PHQ-2 (depression) and GAD-7 (generalized anxiety disorder) scales. The findings indicated that first-generation adolescents from immigrant families were significantly more likely than their second-generation counterparts to report mental-health symptoms, and they also provided worse scores on all measures examined. It was alarming that 42 per cent of the first-generation immigrant group reported that they could not discuss their personal worries with anyone, and more than one-fifth of these youth hardly ever talked about personal matters with their parents. Experienced discrimination was a slightly stronger predictor of generalized anxiety than depressive symptoms and it predicted both symptoms of depression and anxiety more prominently among first-generation immigrant adolescents compared with their second-generation counterparts. Being able to discuss personal matters with parents functioned as a protective factor with similar predictor values in both groups, whereas the possibility of having someone with whom to discuss personal worries was significantly associated to lower levels of anxiety only among first-generation immigrant adolescents.